Peningkatan Efisiensi Produksi UMKM Kacang Telur SAFIA Kabupaten Jember Dengan Penerapan Semi Automatic Filling Machine - Yani Subaktilah; Resti Pranata Putri; Emi Kurniawati (Journal of Community Development, 2025)
UMKM Kacang Telur SAFIA is one of the MSME initiated by the Chamber of Commerce and Industry (KADIN) Jember Regency for the export market exploration program. UMKM Kacang Telur SAFIA has problem in filling egg-coated nut into packaging which is still done manually, where packaging time becomes less efficient and is prone to measurement errors and  deviation of the total weight of the product. The patner hope to improve production efficiency through innovation in filling egg-coated nut into packaging. The solution provided to overcome the obstacles faced by the partner is by introducing and  training in filling egg-coated nut using the Semi Automatic Filling Machine. The implementation methods of this community service program include: surveys, problem formulation, discussions, preparation of training materials, making semi-automatic filling machines,, counseling and introduction to semi-automatic filling machines, training in filling egg-coated nut in packaging using semi-automatic filling machines, counseling on packaging design that appropriates quality standards, and evaluation. The results of the implementation of the community service program for the partner are: 1) There is an increase in the partner knowledge about how to fill egg-coated nut in packaging using a semi-automatic filling machine, 2)  The time efficiency during filling of packaging is up to 2 times faster than manual packaging and the consistency of the weight of egg nut products, 3) the labor load is reduced compared to manual packaging and weighing.